Mycotoxigenic fungi in peanuts from different geographic regions of Egypt - Sultan, Y.; Magan, Naresh (Mycotoxin Research, 2010)
To understand the importance of mycotoxigenic fungi in Egyptian peanuts, samples from five regions (Alexandria, El-Beheira, El-Sharqiya, El-Daqahelaya in northern Egypt and Asyut, southern Egypt) in two seasons (2007, 2008) were collected. Aspergillus was consistently the most frequent genus in seeds and in- shell peanuts and was the dominant mycotoxigenic component of the mycobiota. There was no direct correlation between the moisture content of the samples and the fungal populations on peanut seeds tested from different regions. The most common species were from Aspergillus section Flavi (4.7-78.3%), Aspergillus section Nigri (9.4-52.6%) and Aspergillus section Circumdati (5.1-30.9%). In the in-shell peanut samples the lowest populations were recorded in El-Beheira and Asyut (3.7-4.0 log10 CFU g-1) and the highest in Alexandria and Elsharqiya (4.1- 6.0 log10 CFU g-1). Aspergillus section Flavi and section Nigri were the most dominant and Aspergillus section Circumdati were only found in samples in 2008. Both qualitative (coconut cream agar) and quantitative analyses (HPLC) were used to analyse the potential mycotoxin production by strains isolated from peanuts. Of a total of 88 Aspergillus section Flavi strains examined, 95% were A. flavus based on production of aflatoxin B1 on YES medium and confirmation using molecular analyses. Of 64 Aspergillus section Circumdati strains only 28% produced ochratoxin A (OTA), and were identified as A. westerdijkiae. No Aspergillus section Nigri strains produced OTA, and they were identified as A. niger (uniseriate). The presence of these toxigenic fungi indicates that there is a potential risk of mycotoxin contamination in Egyptian peanuts and suggests that problems can arise from contamination with both aflatoxins, and perhaps also OTA.
Keywords: Peanuts; mycobiota; mycotoxigenic fungi; Aspergillus section Flavi; Aspergillus section Nigri; Aspergillus section Circumdati